Determination of the coefficient of a semilinear parabolic equation for a boundary-value problem with nonlinear boundary condition - Akhundov, A.Ya.; Gasanova, A.I. (Український математичний журнал, 2014)
We study the well-posedness of the inverse problem of determination of the coefficient of a minor term of a semilinear parabolic equation in the presence of a nonlinear boundary condition. The additional condition is given in the nonlocal integral form. A uniqueness theorem and a “conditional” stability theorem are proved. Досліджєно коректність оберненої задачi про визначення коефiцiєнта молодшого члена напівлінійного параболічного рівняння за наявності нелінійної граничної умови. Додаткову умову наведено в нелокальній інтегральній формі. Доведено теорему про єдиність та теорему про „умовну" стійкість.